b ≤ 9 (b is less than or equal to 9)
Hope this helps! ;)
<span>Assuming the graph is y=-3(√2x)-4 and y=-3√(x-4) the transformation would be:
</span><span>The graph is compressed horizontally by a factor of 2
x=1/2x'
</span>y=-3(√2x)-4
y=-3(√x')-4 <span>
</span><span>moved left 4
x=x'-4
</span>y=-3(√x)-4
y=-3(√x'-4)-4
<span>
moved down 4
y=y'-4
</span>y=-3(√x-4)-4
y'-4=-3(√x'-4)-4
y'=-3(√x'-4)-4 +4
y'=-3(√x'-4)
Answer: C. <span>The graph is compressed horizontally by a factor of 2, moved left 4, and moved down 4.
</span>
Answer:
ΔCTA ≅ ΔDRA
Step-by-step explanation:
Triangles CTA and DRA are congruent by ASA postulate. This is because:
- ∠A is the same for both triangles (they are opposite angles)
Then, correspondent angles and sides are congruent, for example, ∠3 ≅ ∠4
Answer:
5
Step-by-step explanation:
5 + 5 = 10
5 x 2 = 10
hope this helps